Modern Trends to Measure the Efficiency and Effectiveness of The Current Budget in Government Units: Analytical Study at Sulaymaniyah University (Raparin Journal of Humanities (RJH), 2025)
The research aims to discuss topics in the financial management of government units, which is how to measure the efficiency and effectiveness of the current budget, and the use of modern methods and techniques in measuring the efficiency and effectiveness of government units, then focusing on the final assessment of the extent to which the desired results are achieved through the use of resources, which includes success in achieving The balance between revenues and expenditures in the long term. The study may use the quantitative approach and the theoretical approach, in addition to reviewing the literature related to the subject and case studies of government units that have succeeded in enhancing the current budget. Countries of the world seek to take into account the reasons for progress by taking advantage of their available capabilities and resources. The budget is prepared the state's public sector is the tool that reflects its strategies in taking advantage of these limited resources and using them. Countries also go through stages of development in their economic, administrative and financial systems, the effects of which are reflected in the structure of their public budgets. From this standpoint comes the importance of the general budget and the necessity of keeping pace with developments in other fields, and as a result of the steady increase in the volume of regional government expenditures and the failure to follow the cash basis in measurement and achieving effective oversight of government performance, and in view of the importance of measuring the transactions of government units on sound accounting foundations and reporting that to all parties. Concerned, specialized accounting professional bodies and organizations, many developed countries and quite a few developing countries have made great efforts to develop the foundations of accounting measurement and disclosure in government units and to follow more efficient and effective methods in preparing budgets. Among the most important conclusions is the use of advanced measurement methods and analytical tools to understand efficiency and effectiveness. And to contribute to enhancing transparency in government units. As for the most important recommendations, government units must be committed to striving towards sustainable and effective financial performance through developing continuous improvement strategies.